Design and analysis of MEMS based capacitive pressure sensor for the detection of colon cancer - Shameem, Syed; Prasad, G.R.K.; Kalyan, G.; Sri varun, H.; Srinivas Babu, P.S. (International Journal of Engineering and Technology, 2017)
Emerging sciences have brought tremendous changes in the electronic world. One such revolutionary technology is MEMS. MEMS extend their implementation into many sectors like mechanical sensors, micro fluids, medical implants, bio-MEMS. In this paper, we discuss the design of a Micro Bio-sensor which senses the capacitance fluctuations materialized in it by various reactions of antigen and antibody. It is a cantilever based structure which is coated with a drug that is responsive to Carcino Embryonic Antigen (CEA), which is considered to be a first level indicator of colon cancer present in human body. The presence of this disease causing element in the blood initiates the antibody-antigen interactions which induces changes in the electrical parameters of the sensor device. These changes are utilized to determine the severity level of pathogens present in the patient’s blood.